Pengaruh Dividend Payout Ratio, Debt To Equity Ratio, Net Profit Margin, Firm Size, Dan Current Ratio Terhadap Price Earning Ratio: Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012 - Sutari Sri Rejeki (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
One of the fundamental analysis that usually used by investors and security analize to value the stock price is by price earning ratio(PER) approach. This research have as a purpose to examine influence factors DPR, DER, NPM, Firm Size, CR to PER. This study aims to examine the factors Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Firm Size, and Current Ratio (CR) of Price Earning Ratio (PER) on Manufacture companies listed in Indonesia Stock Exchange for 2010 - 2012. This study used the entire population of Manufacture companies listed in Indonesia Stock Exchange (BEI) in 2010 until 2012, a total of 396 companies. The samples using 48 companies on manufacturing companies sector. Type of data is secondary data from each manufacturing companies listed on the Indonesia Stock Exchange for three years in 2010, 2011, 2012. The samples are taken by purposive sampling. Data analysis use multiple regression analysis, method which initial by classical test for normality, multicollinearity test, heteroskedastisitas test and autocorrelation test. Hypothesis test is using the F tes, t test, and koefisien determinasi R2. In the classical assumption test results showed that there were no deviations classical assumption, this shows that the available data has been qualified to use multiple linier regression model. From this reseach the following conclusion : the DPR variable is positif and not effect on PER, variabel DER has negative and not effect on PER, NPM variable has negative and not effect on PER, Size variable has positive and effect on PER, and CR variable has positif and not effect on PER. Regression equation obtained is PER =-4.196+0.074 DPR-0.596 DER-0.166 NPM + 0.961 Firm Size+0.245 CR. Coefficient of determination (adjusted R2) is 10 % which means 10 % of PER is influenced by the independent variables, whereas the remaining balance of 90% is explained by other variable not prensented in the study.